Establishing a non-intubated thoracoscopic surgery programme for bilateral uniportal sympathectomy (Swiss Medical Weekly, 2019)
AIM OF THE STUDY Non-intubated, video-assisted thoracoscopic surgery (NiVATS) has been successfully developed in several centres worldwide. Local anaesthesia techniques and techniques to perform thoracoscopic surgery on a spontaneously breathing lung are the two key elements which must be adopted to establish a NiVATS programme. We established NiVATS by performing bilateral, uniportal sympathectomies, and compared it to classical video-assisted thoracoscopic surgery (VATS) under general anaesthesia with double-lumen intubation. METHODS Ten consecutive bilateral VATS sympathectomies were compared with ten consecutive NiVATS procedures. Nineteen of the procedures were for palmar hyperhidrosis and one was for facial blushing. Duration of anaesthesia, surgery and hospitalisation, perioperative complications, side effects and quality of life before and after sympathectomy were analysed. RESULTS Median age was 26.5 years (range 17–55) and mean BMI in the NiVATS group was 21.8 (range 19.1–26.3). NiVATS sympathectomies were performed as outpatient procedures significantly more often (9/10 vs 3/10, p = 0.008). Quality of life was significantly increased after sympathectomy in all patients, with no significant differences between the NiVATS and the VATS groups. There were no differences between the two groups regarding compensatory sweating (40 vs 50%, p = 0.66). The duration of anaesthesia, not including the time required for the surgery, was significantly shorter in the NiVATS group (p